2017
DOI: 10.4236/jbnb.2017.82011
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Synthesis of Zinc Oxide Nanoparticle and its Combined Efficacy with Different Antibiotics against Multidrug Resistant Bacteria

Abstract: Bioinspired synthesis of nanoparticles is a way to synthesize nanoparticles by using biological sources. It's gaining importance due to its ecofriendly, cost effective and large scale production properties. In this present study, the plant Ficus carica was taken to study its ability for synthesizing zinc oxide nanoparticle. The leaf extract of antimicrobial susceptibility showed that most of the antibiotics were resistant towards bacterial isolates of zinc sulphate hepta hydrate and sodium hydroxide, were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Several studies have been undertaken in the field of ZnO-NP synthesis using different biological materials and the authors stated that the synthesis of ZnO-NPs was observed as a white, cloudy haziness in the solution of the reaction mixture, which became deposited at the bottom of the flasks [ 36 , 37 , 38 ]. As the metabolites in each isolate’s CFF may be varied, the results can change, as was the case in this investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been undertaken in the field of ZnO-NP synthesis using different biological materials and the authors stated that the synthesis of ZnO-NPs was observed as a white, cloudy haziness in the solution of the reaction mixture, which became deposited at the bottom of the flasks [ 36 , 37 , 38 ]. As the metabolites in each isolate’s CFF may be varied, the results can change, as was the case in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yusof et al (2020) formed ZnO-NPs via bacterial cells and cell-free filtrate of Lactobacillus plantarum TA4, and the UV-vis absorption spectrum analysis gave absorption peaks at 349 and 351 nm, respectively [ 38 ]. Ehsan and Sajjad (2017) synthesized ZnO-NPs with a 360 nm absorption band using zinc sulfate as a precursor and Ficus carica leaf extract as a reactant [ 37 ]. The TEM and SAED pictures verified the formation of crystalline metal nanostructures and gave more insight into the spherical shape and size features of the metal nanoparticles [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarwar and co-workers demonstrated that nanosized ZnO caused significant oxidative stress to Vibrio cholera , the damage inflicted was DNA degradation, protein leakage, membrane depolarization and fluidity (Sarwar et al, 2016 ). Ehsan and Sajjad, described that ZnO NPs impregnated with antibiotics showed good antibacterial activities against S. aureus, Proteus, Acinetobacter, P. aeruginosa , and E. coli , being that these were resistant to antibiotics but became sensitive in the presence of these NPs with antibiotics (Ehsan and Sajjad, 2017 ). It was also discovered that these NPs induce the production of ROS even in the dark, and this happens due to the surface defects on the NPs.…”
Section: Zinc Oxide (Zno)mentioning
confidence: 99%
“…The impregnation of an antibiotic disc with Ficus carica ‐based zinc oxide NMs resulted in enhanced antibacterial potential compared with a pristine antibiotic. It was then used in combination with multiple antibiotics and tested against different pathogenic bacterial strains, and the results showed a potentiated antimicrobial effect in the presence of NMs (Ehsan & Sajjad, 2017).…”
Section: Applications Of Metallic Green Nmsmentioning
confidence: 99%